Disentangling the stellar populations in the counter-rotating disc galaxy NGC 4550 - Johnston, E; Merrifield, MR; Aragon-Salamanca, A; Cappellari, M (2013)
In order to try and understand its origins, we present high-quality long-slit spectral observations of the counter-rotating stellar discs in the strange S0 galaxy NGC 4550. We kinematically decompose the spectra into two counter-rotating stellar components (plus a gaseous component), in order to study both their kinematics and their populations. The derived kinematics largely confirm what was known previously about the stellar discs, but trace them to larger radii with smaller errors; the fitted gaseous component allows us to trace the hydrogen emission lines for the first time, which are found to follow the same rather strange kinematics previously seen in the [OIII] line. Analysis of the populations of the two separate stellar components shows that the secondary disc has a significantly younger mean age than the primary disc, consistent with later star formation from the associated gaseous material. In addition, the secondary disc is somewhat brighter, also consistent with such additional star formation. However, these measurements cannot be self-consistently modelled by a scenario in which extra stars have been added to initially identical counter-rotating stellar discs, which rules out the Evans and Collett's elegant 'separatrix-crossing' model for the formation of such massive counter-rotating discs from a single galaxy, leaving some form of unusual gas accretion history as the most likely formation mechanism. © 2012 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.